2019
DOI: 10.1111/1756-185x.13468
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in patients with primary antiphospholipid antibody syndrome

Abstract: Aim: Dysregulated apoptosis has been implicated in autoimmune diseases. In the present study, we investigated the apoptosis-related cytokines and apoptosis in patients with primary antiphospholipid syndrome (pAPS). Method: We prospectively recruited 12 pAPS patients, 17 antiphospholipid antibody (APA)-positive systemic lupus erythematosus (SLE) patients without APS manifestations (APA + SLE), 13 SLE patients with secondary APS (APS + SLE) and 10 healthy controls (HCs). Plasma levels of soluble apoptosis-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, pyroptosis and apoptosis are two vital pathways that are implicated in APS pathogenesis. 17,53 A previous study confirmed that active STAT3 upregulates NLRP3 via directly enhancing histone H3 and H4 acetylation at the NLRP3 promoter in LPS-treated macrophages. 45 The upregulated NLRP3 triggered canonical pyroptosis and apoptosis, and also induced the release of proinflammatory cytokines in autoimmune diseases, implying its promising therapeutic potential.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, pyroptosis and apoptosis are two vital pathways that are implicated in APS pathogenesis. 17,53 A previous study confirmed that active STAT3 upregulates NLRP3 via directly enhancing histone H3 and H4 acetylation at the NLRP3 promoter in LPS-treated macrophages. 45 The upregulated NLRP3 triggered canonical pyroptosis and apoptosis, and also induced the release of proinflammatory cytokines in autoimmune diseases, implying its promising therapeutic potential.…”
Section: Discussionmentioning
confidence: 83%
“…STAT3 is a crucial transcriptional regulator of pyroptosis, apoptosis and related inflammation. Moreover, pyroptosis and apoptosis are two vital pathways that are implicated in APS pathogenesis 17,53 . A previous study confirmed that active STAT3 upregulates NLRP3 via directly enhancing histone H3 and H4 acetylation at the NLRP3 promoter in LPS‐treated macrophages 45 .…”
Section: Discussionmentioning
confidence: 87%
“…Apoptosis is implicated in the pathogenesis of APS. Some controversy exists, since exposed anionic phospholipids during apoptosis may provide B2GPI binding sites, which then induce the generation of aPL [ 58 ]. Bondanza et al reported that autoimmunity, including anti-B2GPI IgG, would develop in mice only when apoptotic cells/B2GPI are injected along with syngeneic DCs [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although cleavage of vimentin by caspases is a requisite for apoptosis, 93 evidence regarding this dysregulation process of apoptosis in APS patients has not been proven. 95 …”
Section: Pathogenetic Mechanisms In Apsmentioning
confidence: 99%
“…Although cleavage of vimentin by caspases is a requisite for apoptosis, 93 evidence regarding this dysregulation process of apoptosis in APS patients has not been proven. 95 Finally, platelets are also activated by NETs, specifically by histones. These proteins activate platelets expressing phosphatidylserine, P-selectin, and FVa on their surface.…”
Section: Platelet Activation Mediated By Aplsmentioning
confidence: 99%